An organic compound containing phenanthroline and phosphine substituents and an organic electroluminescent device containing the same
By using organic compounds containing phenanthroline and phosphine substituents in the N-type charge generation layer material, the problem of insufficient electron mobility and thermal stability is solved, and the equilibrium and thermal stability of carrier transport are improved, reducing the The driving voltage of the stacked organic electroluminescent device extends its life.
Patent Information
- Application Number
- CN202411533376.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The electron mobility and thermal stability of the existing N-type charge generation layer materials are insufficient, resulting in limited performance of stacked organic electroluminescent devices, affecting their development and commercialization.
Using organic compounds containing phenanthroline and phosphine substituents as the N-type charge generation layer material, by adding electron-deficient dibenzofuran/dibenzothiophene or derivative fragments thereof between the phenanthroline and phosphine fragments, Improve the HOMO and LUMO distribution of molecules, improve electron mobility and improve thermal stability.
Effectively match the transmission rate of electrons and holes, promote carrier transmission balance, reduce driving voltage, significantly improve the thermal stability of the material, and extend device life.
Smart Images

Figure CN119039349B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of OLED, and specifically comprises an organic compound containing phenanthroline and a phosphine substituent and an organic electroluminescent device comprising the same. Background Art
[0002] The stacked organic electroluminescent device is composed of two or more independent electroluminescent units connected in series through a charge generation layer. The light-emitting principle of the stacked organic electroluminescent device is: when a voltage is applied, the holes provided by the anode and the electrons provided by the N-type charge generation layer recombine to form excitons. At the same time, the holes provided by the P-type charge generation layer and the electrons provided by the cathode recombine to form excitons. In other words, when the number of carriers is equal, the stacked organic electroluminescent device can form double excitons, which can theoretically increase the brightness and current efficiency exponentially. The more light-emitting units there are in the stacked organic electroluminescent device, the higher its brightness and current efficiency will be. However, its turn-on voltage will also increase with the increase of light-emitting units, so the power efficiency will not be significantly improved. Compared with traditional organic electroluminescent devices, stacked organic electroluminescent devices have the advantages of high brightness, high contrast, low power consumption, etc., and are widely used in the display field.
[0003] In the prior art, commonly used N-type charge generation layer materials include conjugated polymers, small molecule organic compounds, organic metal complexes, etc. Conjugated polymers have good carrier transport properties and optical properties, but their preparation process is complicated and the cost is high; small molecule organic compounds have a simple preparation process and low cost, but the electron-rich characteristics of small molecule organic compounds themselves lead to their hole transport ability being better than electron transport ability. Therefore, commonly used small molecule organic compounds often have problems of poor electron transport ability and unbalanced carrier transport. Electron mobility refers to the speed of movement of electrons in a material under the action of an external electric field, and is one of the important factors affecting the charge injection efficiency and the performance of stacked organic electroluminescent devices. At present, the electron mobility and thermal stability of N-type charge generation layer materials are one of the key factors affecting the performance of stacked organic electroluminescent devices. This seriously restricts the development and commercialization of stacked organic electroluminescent devices. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides an organic compound containing phenanthroline and a phosphine substituent and an organic electroluminescent device containing the same.
[0005] To achieve the above objectives, the technical solutions adopted by the present invention include:
[0006] The first aspect of the present invention provides an organic compound containing phenanthroline and a phosphine substituent, wherein the organic compound is selected from the general structural formula shown in the following formula I:
[0007] I;
[0008] wherein R1 represents a single substituent to the maximum permissible substituent selected from hydrogen or phenyl;
[0009] L1 is selected from the general structural formula shown in Formula II:
[0010] II;
[0011] Ring A and Ring B are selected from any one of an aryl group having 6 to 30 carbon atoms, a heteroaryl group having 5 to 30 carbon atoms, a condensed ring aryl group having 10 to 30 carbon atoms, and a condensed ring heteroaryl group having 9 to 30 carbon atoms;
[0012] One of X1 and X2 is selected from O or S, and the other is selected from any one of a single bond, a substituted or unsubstituted alkyl group having 1 to 5 carbon atoms; when X1 and X2 have a substituent, the substituent is selected from an alkyl group having 1 to 5 carbon atoms;
[0013] L2 represents any one of a single bond, an aryl group having 6 to 30 carbon atoms, and a condensed ring aryl group having 6 to 30 carbon atoms;
[0014] In formula I and formula II, any hydrogen can be replaced by deuterium, and any nitrogen can be replaced by 15 N substitution, any sulfur can be 33 S. 34 S or 36 S is substituted, any oxygen can be 17 O or 18 O substitution, any carbon can be 13 C substituted.
[0015] Furthermore, the organic compound is selected from one of the general structural formulas shown in the following formulas I-1 to I-10:
[0016] I-1, I-2, I-3, I-4, I-5, I-6, I-7, I-8, I-9, I-10.
[0017] Furthermore, the L1 is selected from one of the following structures:
[0018] .
[0019] Furthermore, the L1 is selected from one of the following structures:
[0020] .
[0021] Furthermore, the L1 is selected from one of the following structures:
[0022] .
[0023] Furthermore, one of X1 and X2 represents O.
[0024] Furthermore, in the representations of X1 and X2, the substituted or unsubstituted alkyl group having 1 to 5 carbon atoms is selected from methylene groups substituted or unsubstituted by methyl groups.
[0025] Furthermore, L2 represents any one of a single bond, a phenyl group, and a naphthyl group.
[0026] Furthermore, the organic compound is selected from one of the following structures:
[0027] .
[0028] The second aspect of the present invention provides an organic electroluminescent device, comprising an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more organic compounds as described above.
[0029] Furthermore, the charge generation region includes an N-type charge generation layer and a P-type charge generation layer, the N-type charge generation layer is located between the P-type charge generation layer and the first electron transport region, wherein the N-type charge generation layer includes one or more organic compounds as described above.
[0030] Beneficial effects of the present invention:
[0031] The hole transport capacity of existing organic electroluminescent materials is generally stronger than the electron transport capacity. The organic compound containing phenanthroline and phosphine substituents provided by the present invention can improve the electron mobility of the material by adding electron-deficient dibenzofuran / dibenzothiophene or its derivative fragments between the phenanthroline and phosphine-containing fragments, so as to match the transmission rates of electrons and holes and promote carrier transmission balance.
[0032] Furthermore, in the organic compound provided by the present invention, the phenanthroline and phosphine-containing fragments are arranged in a para position on both sides of the dibenzofuran / dibenzothiophene or its derivative fragment. On the one hand, this special connection method can effectively improve the distribution of HOMO and LUMO of the molecule, improve the overlap of the material, and can improve the electron transmission caused by π-π stacking between the material molecules, thereby improving the electron mobility of the material; on the other hand, this special connection method is also conducive to the formation of hydrogen bonds between the dibenzofuran / dibenzothiophene or its derivative fragment and the connecting groups at both ends, thereby reducing the deformation of the structure when heated, increasing the glass transition temperature, and thus improving the thermal stability of the material.
[0033] The organic compound containing phenanthroline and phosphine substituents provided by the present invention is used as an N-type charge generation layer material in the charge generation layer of a stacked organic electroluminescent device. The N-type charge generation layer material can not only improve the overlap of the material, improve the electron transmission caused by π-π stacking between material molecules, and improve the electron mobility of the material, but also effectively balance the carrier transmission and injection capabilities of the material, thereby reducing the driving voltage of the stacked organic electroluminescent device. The N-type charge generation layer material has a high glass transition temperature and high thermal stability, and can effectively extend the life of the stacked organic electroluminescent device. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic structural diagram of the organic electroluminescent device of the present invention. DETAILED DESCRIPTION
[0035] In order to more clearly understand the content of the present invention, it will be described in detail with reference to the drawings and embodiments.
[0036] The organic compound of the present invention is suitable for use in light-emitting elements, display panels and electronic devices, and is particularly suitable for use in organic electroluminescent devices. The electronic device of the present invention is a device comprising a layer of at least one organic compound, and the device may also comprise an inorganic material or a layer formed entirely of an inorganic material. The electronic device is preferably an organic electroluminescent device (OLED). The schematic structural diagram of an exemplary organic electroluminescent device is shown in FIG. Figure 1 shown.
[0037] Experimental Section
[0038] In order to understand the content of the present invention more clearly, the luminescent characteristics of the organic compound, the preparation method of the organic compound and the device will be explained in detail in conjunction with the examples. Various chemical reactions can be applied to the synthetic method of the compound of one embodiment of the present invention. However, it should be noted that the synthetic method of the compound of one embodiment of the present invention is not limited to the synthetic method described below. Unless otherwise indicated, the subsequent synthesis is carried out in anhydrous solvent under a protective gas atmosphere. Solvents and reagents can be purchased from conventional reagent suppliers.
[0039] Synthesis of compounds
[0040] Synthesis Example 1
[0041]
[0042] In a three-necked flask, compound Sub-2 (23.66 g, 100 mmol) and 250 ml of anhydrous tetrahydrofuran were added and stirred to dissolve. Under nitrogen protection, the reaction system was cooled to -78 °C, and 40 ml of n-butyl lithium (2.5 N) was slowly added dropwise. After that, the reaction system was stirred at -78 °C for 1 hour, and then Sub-1 (28.15 g, 100 mmol) was dissolved in 150 ml of anhydrous tetrahydrofuran and slowly added dropwise to the reaction system at -78 °C. After that, the reaction system was stirred at room temperature for 2 h. The reaction was quenched with 1000 ml of dilute hydrochloric acid (0.1 N), and the product was extracted with ethyl acetate. After separation, the organic phase was dried over anhydrous sodium sulfate and the solvent was removed by rotary evaporation. The crude product was purified by column chromatography to obtain the product Sub-3: 30.61 g, with a yield of 76%, MS (m / z) (M+): 612.
[0043] Sub-3 (30.61 g, 76 mmol), biboronic acid pinacol ester (21.33 g, 84 mmol) and potassium acetate (8.24 g, 84 mmol) were added to 300 ml of 1,4-dioxane, and then tetrakistriphenylphosphine palladium (2.3 g, 2 mmol) was introduced under nitrogen protection. The reaction system was then heated to 110 ° C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried with anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 10:1 (v / v) column. The final product Sub-4 was obtained: 21.75 g, yield: 58%, MS (m / z) (M+): 494.
[0044] Sub-4 (21.75 g, 44 mmol), 2-phenyl-9-bromo-1,10-phenanthroline (14.75 g, 44 mmol) and potassium carbonate (7.31 g, 53 mmol) were added to a mixed solution of 300 ml toluene and water, wherein the volume ratio of toluene to water was 4:1, and then tetrakistriphenylphosphine palladium (3.5 g, 3 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried with anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by using a column eluent of petroleum ether / dichloromethane = 10:1 (v / v). Finally, product A1 was obtained: 16.98 g, yield: 62%, MS (m / z) (M+): 622.
[0045] Synthesis Example 2
[0046]
[0047] The same method as in Synthesis Example 1 was used, using A2 (23.46 g, 40 mmol) and B2 (10.36 g, 40 mmol) as raw materials to finally obtain product C2: 19.99 g (yield: 78%), MS (m / z) (M+): 639.
[0048] Synthesis Example 3
[0049]
[0050] The same method as in Synthesis Example 1 was used, using A3 (22.82 g, 40 mmol) and B3 (10.36 g, 40 mmol) as raw materials to finally obtain product C3: 16.49 g (yield: 66%), MS (m / z) (M+): 623.
[0051] Synthesis Example 4
[0052]
[0053] The same method as in Synthesis Example 1 was used, using A4 (22.82 g, 40 mmol) and B4 (13.41 g, 40 mmol) as raw materials to finally obtain product C4: 21.09 g (yield: 75%), MS (m / z) (M+): 699.
[0054] Synthesis Example 5
[0055]
[0056] The same method as in Synthesis Example 1 was used, using A5 (24.82 g, 40 mmol) and B5 (10.36 g, 40 mmol) as raw materials to finally obtain product C5: 14.16 g (yield: 53%), MS (m / z) (M+): 673.
[0057] Synthesis Example 6
[0058]
[0059] The same method as in Synthesis Example 1 was used, using A6 (24.82 g, 40 mmol) and B6 (13.41 g, 40 mmol) as raw materials to finally obtain product C6: 22.09 g (yield: 74%), MS (m / z) (M+): 749.
[0060] Synthesis Example 7
[0061]
[0062] The same method as in Synthesis Example 1 was used, using A7 (22.82 g, 40 mmol) and B7 (13.41 g, 40 mmol) as raw materials to finally obtain product C7: 20.57 g (yield: 74%), MS (m / z) (M+): 699.
[0063] Synthesis Example 8
[0064]
[0065] The same method as in Synthesis Example 1 was used, using A8 (24.82 g, 40 mmol) and B8 (13.41 g, 40 mmol) as raw materials to finally obtain product C8: 20.55 g (yield: 69%), MS (m / z) (M+): 749.
[0066] Synthesis Example 9
[0067]
[0068] The same method as in Synthesis Example 1 was used, using A9 (24.82 g, 40 mmol) and B9 (10.36 g, 40 mmol) as raw materials to finally obtain product C9: 15.23 g (yield: 57%), MS (m / z) (M+): 673.
[0069] Synthesis Example 10
[0070]
[0071] The same method as in Synthesis Example 1 was used, using A10 (24.86 g, 40 mmol) and B10 (10.36 g, 40 mmol) as raw materials to finally obtain product C10: 18.82 g (yield: 70%), MS (m / z) (M+): 674.
[0072] Synthesis Example 11
[0073]
[0074] The same method as in Synthesis Example 1 was used, using A11 (22.86 g, 40 mmol) and B11 (13.41 g, 40 mmol) as raw materials to finally obtain product C11: 21.27 g (yield: 76%), MS (m / z) (M+): 700.
[0075] Synthesis Example 12
[0076]
[0077] The same method as in Synthesis Example 1 was used, using A12 (24.5 g, 40 mmol) and B12 (13.41 g, 40 mmol) as raw materials to finally obtain product C12: 23.28 g (yield: 79%), MS (m / z) (M+): 741.
[0078] Comparative Examples 1-3
[0079] The structures of the compounds tried during the research are shown below:
[0080]
[0081] Material performance evaluation
[0082] Due to the electron-rich nature of organic molecules, their hole transport ability is often better than their electron transport ability. Therefore, compared with hole transport materials, electron transport materials with excellent performance are more scarce. For n-CGL materials, their performance is closely related to their electron transport ability. In general, an ideal n-CGL material requires the following characteristics:
[0083] 1. High electron mobility, which matches the electron and hole transfer rates and promotes carrier transfer balance;
[0084] Rigid planar molecules have strong intermolecular π-π interactions, so they are often used as electron transport materials. Rigid planar carrier transport materials usually have high mobility only in the direction of π-π stacking. By increasing the overlap of the material, that is, the overlap range of the HOMO and LUMO orbitals, the electron transport caused by π-π stacking between material molecules can be improved, thereby improving the electron mobility of the material.
[0085] In order to characterize the degree of distortion of the organic compound molecules provided by the present invention, Overlap calculation was performed on the molecular structure prepared in the above specific implementation mode, and the results are shown in Tables 1-1 to 1-4; for heteroaromatic ring structures containing condensed rings or electron-withdrawing, the larger the Overlap value, the better the overlap between the HOMO and LUMO orbitals of the compound, which to a certain extent can reflect that the distribution range of the LUMO molecular orbital of the material on the molecule is larger, that is, the proportion of the compound that transmits electrons is larger, and thus it is more conducive to the transmission of electrons.
[0086] 2. Good thermal stability, able to maintain stable molecular structure and transport layer morphology during device operation.
[0087] Glass transition refers to a reversible transition of an amorphous region in an amorphous polymer or a semi-crystalline polymer from a hard, relatively brittle glass state to a viscous flow state or a rubber state during heating. The glass transition temperature is the temperature at which the glass transition occurs. A lower glass transition temperature can cause the film layer of the device to be unstable during heat treatment, resulting in poor display. In order to characterize the thermal stability of the organic compound molecules provided by the present invention, the glass transition temperatures of the example compounds and the comparative example compounds were tested by differential scanning calorimetry of thermal analysis using NETSZSCH DSC214. The specific test results are shown in Tables 1-1 to 1-4.
[0088] Table 1-1
[0089]
[0090] Table 1-2
[0091]
[0092] Table 1-3
[0093]
[0094] Table 1-4
[0095]
[0096] It can be seen from the data of Table 1-1 to Table 1-4 that, compared with the comparative example compounds, the Overlap value and glass transition temperature of the organic compound containing phenanthroline and phosphine substituent provided by the present invention are both higher, indicating that the organic compound provided by the present invention has higher electron mobility and higher thermal stability. The organic compound containing phenanthroline and phosphine substituent provided by the present invention forms a para-substituted structure by arranging the phenanthroline and phosphine-containing fragments in a para position on both sides of the dibenzofuran and its derivative fragments, which can effectively improve the distribution of HOMO and LUMO of the molecule, improve the Overlap of the material, and improve the electron transmission caused by π-π stacking between the material molecules, thereby improving the electron mobility of the material; on the other hand, the special connection mode is also conducive to the formation of hydrogen bonds between the dibenzofuran and its derivative fragments and the connecting groups at both ends, reducing the deformation of the structure when heated, and increasing the glass transition temperature, thereby improving the thermal stability of the material.
[0097] Fabrication and characterization of OLEDs
[0098] Device Embodiment
[0099] The organic electroluminescent device provided by the present invention comprises an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer which are sequentially arranged on a substrate;
[0100] Further, the first hole transport region includes a hole injection layer, a first hole transport layer and a first electron blocking layer; the first electron transport region includes a first hole blocking layer and a first electron transport layer; the charge generation region includes an N-type charge generation layer and a P-type charge generation layer; the second hole transport region includes a second hole transport layer and a second electron blocking layer; the second electron transport region includes a second hole blocking layer, a second electron transport layer and an electron injection layer.
[0101] Furthermore, the light-emitting layer is composed of a main material and a doping material, and the main material of the light-emitting layer can be composed of one molecular material or multiple molecular materials.
[0102] The deuterated organic compound of the present invention can be used in one or more layers of the above-mentioned organic electroluminescent device, preferably in the N-type charge generation layer material of the device.
[0103] The anode in the embodiment adopts anode materials commonly used in the art, such as ITO, Ag or their multilayer structures. The hole injection layer adopts hole injection materials commonly used in the art, and F4TCNQ, HATCN, NDP-9, etc. are added for doping. The hole transport layer adopts hole transport materials commonly used in the art. The light-emitting layer adopts light-emitting materials and doping materials commonly used in the art, for example, it can be composed of a main material and a doping material. The electron transport layer adopts electron transport materials commonly used in the art. The electron injection layer adopts electron injection materials commonly used in the art, such as Liq, LiF, Yb, etc. The N-type charge generation layer material adopts a deuterated organic compound provided by the benzene invention. The cathode adopts materials commonly used in the art, such as metal Al, Ag or metal mixtures (Ag-doped Mg, Ag-doped Ca, etc.).
[0104] The electrode preparation method and the deposition method of each functional layer in this embodiment are conventional methods in the art, such as vacuum thermal evaporation or inkjet printing, etc., which will not be described in detail here. Only some process details and test methods in the preparation process are supplemented as follows:
[0105] Device Example 1
[0106] The substrates used in the present invention were subjected to the following operations: the ITO substrate was patterned so that its luminous area had a size of 3 mm×3 mm, and then water / isopropanol ultrasound, UV / ozone irradiation, and then dried at 100°C. After that, the ITO substrate was mounted on a substrate holder of a vacuum deposition device and the pressure was adjusted so that the vacuum rate became 1×10-7 torr.
[0107] Then, the following operations were performed: first, HTL-1 and p-dopant-1 (the mass ratio of HTL-1 to p-dopant-1 was 97:3) were vacuum deposited on the ITO layer (anode) formed on the substrate with a thickness of 10 nm to form a hole injection layer; secondly, HTL-1 was vacuum deposited on the hole injection layer with a thickness of 20 nm to form a first hole transport layer; secondly, EB-1 was vacuum deposited on the first hole transport layer with a thickness of 5 nm to form a first electron blocking layer; thirdly, a mixture of BH-1 and BD-1 was vacuum deposited on the first electron blocking layer with a thickness of 20 nm to form a first light-emitting layer. , wherein BH-1 is used as the host and BD-1 is used as the dopant, and the mass ratio of the host to the dopant is 98:2; then, on the first light-emitting layer, HB-1 is vacuum deposited with a thickness of 5 nm to form a first hole blocking layer; then, on the first hole blocking layer, ET-01:Liq (the mass ratio of ETL-1 to Liq is 1:1) is vacuum deposited with a thickness of 15 nm to form a first electron transport layer; then, on the first electron transport layer, C1 and Yb (the mass ratio of C1 to Yb is 98:2) are vacuum deposited with a thickness of 15 nm to form an N-type charge generation layer, and HTL-1 and p-d are vacuum deposited with a thickness of 10 nm. opant-1 (the mass ratio of HTL-1 to p-dopant-1 is 97:3) to form a P-type charge generation layer, and then on the above hole generation layer, HTL-1 is vacuum deposited with a thickness of 20nm to form a second hole transport layer, and then on the above second hole transport layer, EB-1 is vacuum deposited with a thickness of 5nm to form a second electron blocking layer, and then on the above second electron blocking layer, a mixture of BH-1 and BD-1 is vacuum deposited with a thickness of 20nm to form a second light-emitting layer, wherein BH-1 is used as a host and BD-1 is used as a dopant, and the mass ratio of the host to the dopant is 98:2; then on the above second light-emitting layer, a mixture of BH-1 and BD-1 is vacuum deposited with a thickness of 20nm to form a second light-emitting layer. The method comprises the following steps: first, vacuum depositing HB-1 with a thickness of 5 nm on the cathode layer to form a second hole blocking layer; then vacuum depositing ET-01 and Liq (the mass ratio of ETL-1 to Liq is 1:1) with a thickness of 15 nm on the second hole blocking layer to form a second electron transport layer; then depositing Yb with a thickness of 1 nm on the second electron transport layer to form an electron injection layer, and then depositing Mg and Ag (the mass ratio of Mg to Ag is 1:9) with a thickness of 15 nm on the electron injection layer to form a cathode, and then depositing CPL-1 with a thickness of 50 nm on the cathode to form a covering layer, thereby preparing a stacked organic electroluminescent device.
[0108] In addition to the materials used in the present invention, the molecular structures of the remaining layers of the device are as follows:
[0109] .
[0110] Device Examples 2-12
[0111] The above method is used to prepare the compound described in the example into an organic electroluminescent device, wherein C2 to C12 are used to replace C1 to prepare organic electroluminescent device examples 2-12.
[0112] Device Comparison Examples 1-3
[0113] The above method was used to prepare the compounds described in the examples into organic electroluminescent devices, wherein D1 to D3 were used to replace C1 to prepare organic electroluminescent device comparative examples 1-3.
[0114] The OLED devices described above were tested by standard methods. For this purpose, at J = 10 mA / cm 2 The driving voltage, brightness, electroluminescent current efficiency (measured in cd / A) and external quantum efficiency (EQE, measured in percentage) of the organic electroluminescent device are determined at a current density of 200 mA / cm2, which is calculated from the current / voltage / luminescent density characteristic line (IVL characteristic line) showing Lambertian emission characteristics as a function of luminous density. The lifetime LT is defined as the time after which the brightness drops from the initial luminous brightness L0 to a specific proportion L1 when operating at a constant current J; J = 20 mA / cm2 2 The expression L1 = 90% means that at 20 mA / cm 2 When working under LT, the luminance drops to 90% of its initial value L0 after time LT. Similarly, J = 20 mA / cm 2 , L1 = 95% means, at 20mA / cm 2 When working under LT, the luminous brightness drops to 95% of its initial value L0 after time LT.
[0115] The data of various OLED devices are summarized in Table 2-1 to Table 2-4. The various parameters of the device examples and the device comparison examples are compared to show the performance data of various OLED devices.
[0116] The test instruments and methods for testing the performance of the OLED devices in the above embodiments and comparative examples are as follows:
[0117] Quantum efficiency CE (cd / A) and color coordinates (CIEy) were tested using a spectrum scanner PhotoResearch PR-635;
[0118] Current density and lighting voltage: tested using a digital source meter Keithley 2400;
[0119] Blue index is obtained by dividing the quantum efficiency CE (cd / A) by the color coordinate (CIEy);
[0120] Life test: Use LT-96ch life test device.
[0121] The performance test results of the above devices are listed in Table 2-1 to Table 2-4.
[0122] Table 2-1 Device performance test results
[0123]
[0124] Table 2-2 Device performance test results
[0125]
[0126] Table 2-3 Device performance test results
[0127]
[0128] Table 2-4 Device performance test results
[0129]
[0130] It can be seen from the above device results that compared with the comparative compound D1, the organic compound provided by the present invention can significantly improve the material energy level distribution by arranging the phenanthroline and the phosphine-containing fragment in a para position on both sides of the dibenzofuran and its derivative fragments, thereby reducing the driving voltage of the material. Compared with the comparative compound D2, the organic compound provided by the present invention contains phenanthroline and phosphine-containing fragments with high electron transmission ability at both ends of the structure, and the dibenzofuran / dibenzothiophene or its derivative fragments located at the center of the structure have electron deficiency, which can significantly improve the ability of carrier transmission and injection, thereby improving the electron mobility, and the para-substituted phosphine substituent can make the LUMO of the material more evenly distributed on the material structure through its electron pulling effect, thereby reducing the driving voltage of the material. Compared with the comparative compound D3, the organic compound provided by the present invention introduces dibenzofuran, dibenzothiophene or its derivative groups between the phenanthroline and the phosphine-containing fragments, so that the central connecting part and the aromatic group on the phenanthroline or phosphine side are more likely to form hydrogen bonds, thereby improving the thermal stability of the material.
[0131] The organic compound containing phenanthroline and phosphine substituents provided by the present invention is used as an N-type charge generation layer material in the charge generation layer of a stacked organic electroluminescent device. The N-type charge generation layer material can not only improve the overlap of the material, improve the electron transmission caused by π-π stacking between material molecules, and improve the electron mobility of the material, but also effectively balance the carrier transmission and injection capabilities of the material, thereby reducing the driving voltage of the stacked organic electroluminescent device. The N-type charge generation layer material has a high glass transition temperature and high thermal stability, and can effectively extend the life of the stacked organic electroluminescent device.
[0132] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. An organic compound containing phenanthroline and a phosphine substituent, characterized in that: The organic compound is selected from the general structural formula shown in the following formula I: I; wherein R1 represents a single substituent to the maximum permissible substituent selected from hydrogen or phenyl; L1 is selected from one of the following structures: ; L2 represents any one of a phenyl group and a naphthyl group.
2. The organic compound according to claim 1, characterized in that The organic compound is selected from one of the general structural formulas shown in the following formulas I-1 to I-10: I-1、 I-2、 I-3、 I-4、 I-5、 I-6、 I-7、 I-8、 I-9、 I-10。 3. The organic compound according to claim 1, characterized in that The organic compound is selected from one of the following structures: 。 4. An organic electroluminescent device, characterized in that: It includes an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more organic compounds as described in any one of claims 1 to 3.
5. The organic electroluminescent device according to claim 4, characterized in that: The charge generation region includes an N-type charge generation layer and a P-type charge generation layer, the N-type charge generation layer is located between the P-type charge generation layer and the first electron transport region, wherein the N-type charge generation layer includes one or more organic compounds as described in any one of claims 1 to 3.
Citation Information
Patent Citations
OLED luminescent compound, organic electroluminescent element and application
CN118084974A